LETHAL FUNGAL AORTITIS IN SURGICALLY CORRECTED SUPRAVALVULAR AORTIC STENOSIS IN A CHILD WITH WILLIAMS SYNDROME - Ayesha Butt,; Naela Ashraf,; Khuzaima Tariq,; Muneer Amanullah, (Journal of Ayub Medical College Abbottabad, 2023)
Williams syndrome (WS), is a multisystem disorder occurring in 1 in 10,000 live births with supravalvular aortic stenosis (SVAS) being the most common cardiovascular manifestation. We present the case of a 2.5 years old male, known case of WS who presented with cognitive delay, history of right-sided stroke and left hemiplegia. Echocardiography revealed severe SVAS with a gradient of 105 mmHg. Diameter of the Sino tubular junction was 4 mm. Computerized tomography angiogram showed diffuse stenosis of ascending aorta with intraluminal thrombus. At surgery, the ascending aorta was augmented with autologous pericardial patches and end-to-end anastomosis of the proximal and distal aorta completed the reconstruction. The patient was discharged in a stable condition. He presented 6 weeks post-op with a pulsating pseudoaneurysm through the sternal wound. Emergency surgery with removal of fungal vegetation and reconstruction of the ascending aorta was performed. He expired due to fungal sepsis a week later.